Nanoliposomal L-Asparaginase and Its Antitumor Activities in Lewis Lung Carcinoma Tumor-Induced BALB/c Mice - Thi Thao Do; Thi Phuong Do; Thi Nga Nguyen; Thi Cuc Nguyen; Thi Thu Phuong Vu; Thi Giang An Nguyen (Advances in Materials Science and Engineering)
Although L-Asparaginase (L-ASP) is an effective chemotherapeutic agent, it has side effects such as fever, skin rashes, chills, anaphylaxis, and severe allergic reactions. Moreover, the short half-life of L-ASP reduces its antitumor activity. To reduce its side effects and broaden its pharmaceutical applications, L-ASP obtained from Pectobacterium carotovorum was subjected to liposomal conjugation. The enzyme was then loaded into liposomes using the hydrated thin-film method. The in vitro cytotoxic activity of liposomal L-ASP was evaluated with the MTT assay using cancerous cell lines, and its antitumor effects were examined in Lewis lung carcinoma (LLC) tumorized mice. The average size of the liposomes containing purified L-asparagine was 93.03 ± 0.49 nm. They had a zeta potential of –15.45 ± 6.72 mV, polydispersity index of 0.22 ± 0.02, and encapsulation efficiency of 53.99 ± 5.44%. The in vitro cytotoxic activity of liposomal L-ASP was less effective against LLC, MCF-7 (human breast carcinoma), HepG2 (human hepatocellular carcinoma), SK-LU-1 (human lung carcinoma), and NTERA-2 (pluripotent human embryonic carcinoma) cells than that of free L-ASP. However, the antitumor activity of liposomal L-ASP was significantly greater than that of untrapped L-ASP at the same doses (6 UI/mouse) in terms of tumor size (6309.11 ± 414.06 mm3) and life span (35.00 ± 1.12 days). This is the first time the antitumor activities of PEGylated nanoliposomal L-ASP have been assessed in LLC carcinoma tumor-induced BALB/c mice and showed significantly improved pharmacological properties compared to those of free L-ASP (P<0.05). Thus, nanoliposomal L-ASP should be considered for its widening applications against carcinoma tumors.